ORGANIZATION OF MEDICAL CARE FOR PREGNANT WOMEN IN HIGH: RISK GROUPS - Gulammaxmudova, D.V.; Nazarova , S.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The health of women and children is one of the key indicators of a country’s socio-economic development and overall societal well-being. The course of pregnancy and its impact on both the mother and the newborn largely depend on the woman’s age, especially when giving birth for the first time. Properly organized perinatal care based on modern medical technologies is one of the most important conditions for ensuring safe motherhood and favorable outcomes for both mother and child. Identifying medical and social risk factors that may negatively affect reproductive health plays a crucial role in planning adequate medical care for pregnant women at the regional level. Moreover, recognizing these factors allows for individual assessment of women’s reproductive health and the prevention of potential complications during pregnancy and childbirth. The main goal of this study is to investigate perinatal risk factors in women giving birth for the first time at an advanced reproductive age and to develop an effective system of medical care for this group. The research employed historical, sociological, and statistical methods, along with expert evaluation techniques. A thorough analysis was conducted on the health status, medical activity, and the quality of medical care provided to women giving birth for the first time at a later reproductive age. The findings indicate that this group of women tends to have a lower level of somatic and gynecological health, and pregnancy and childbirth are often accompanied by various complications. Additionally, health problems are frequently observed among the newborns of both older and younger mothers. Therefore, women giving birth at an advanced age should be classified as a high perinatal risk group, requiring dispensary monitoring and a specialized approach during labor and delivery